Code Compliance in Reinforce Concrete Design: A Comparative Study of USA Code (ACI) and Chinese Code (GB) - Lan Zhang; Hao Hu; Yi Fang; Zhenyu Qiang (Advances in Civil Engineering)
The structural engineering codes dictate the design criteria of the facility. Given that different countries use different parameters to design a facility, different codes are followed. Current code comparison focus on the clauses analysis in the code gives theoretical guideline. When the US facility design team needs to make a decision to follow which code to in China, the current study cannot provide a business decision input. This study evaluates the design process to illustrate when and where the codes will be applied and calculated through a design process where the loading and coefficient factors of different codes are analyzed. Software programs built-in codes are then used to design the structure to obtain the structure result in terms of volume of the concrete and weight of the rebar being calculated. The study also presents a case study and calculates that the United States code uses 8–10% more rebar compared to the Chinese code. The study result can be a reference for the project management team who has to make a business decision over which code to be followed at what cost. The paper also identifies the choice of the seismic coefficient factor has a significant impact on the usage of the rebar and might be justified for the future study.